2019
DOI: 10.29333/ejmste/115016
|View full text |Cite
|
Sign up to set email alerts
|

Secondary School Biology Students’ Attitudes towards Modern Biotechnology Characterised using Structural Equation Modeling

Abstract: In biotechnology education research (BTER), the multifaceted construct of attitude has seldom been problematised in depth despite that the majority of studies in BTER during the last two decades have focused on students' attitudes towards modern biotechnology. Most studies on attitudes in science education use a single-factor model in characterising students' attitudes, while some use a three-factor model. By means of structural equation modeling the current study tested and evaluated single, three-factor, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 56 publications
1
3
0
Order By: Relevance
“…A long time ago, it was noted that the classroom environment presented more relation with the student's attitude towards a science that includes biology (Talton & Simpson, 1987). The findings relate with those of other studies, such as those of Nordqvist and Johansson (2020), , Prokop, Tuncer, et al (2007), and Sanders and Morrison-Shetlar (2001). They noted that, in general, students have a positive attitude towards biology.…”
Section: Discussionsupporting
confidence: 56%
“…A long time ago, it was noted that the classroom environment presented more relation with the student's attitude towards a science that includes biology (Talton & Simpson, 1987). The findings relate with those of other studies, such as those of Nordqvist and Johansson (2020), , Prokop, Tuncer, et al (2007), and Sanders and Morrison-Shetlar (2001). They noted that, in general, students have a positive attitude towards biology.…”
Section: Discussionsupporting
confidence: 56%
“…Based on the study results, it was also known that attitudes toward genetic engineering were found to be different in male and female students. Males showed a more positive attitude toward genetic engineering applications than female students (Meerah et al, 2012;Nordqvist & Johansson, 2020). Science subjects that were taken also influenced students' attitudes toward genetic engineering.…”
Section: Philippinesmentioning
confidence: 97%
“…That said, the ABC model remains at the forefront of the widely contested topic of attitude's influence upon individual behaviour (e.g. Haddock and Maio 2019;Nordqvist and Johansson 2020).…”
Section: Defining Attitudementioning
confidence: 99%